ANALISIS RASIO ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI KARYAWAN ANGKASA PURA 1 “SELAPARANG” BANDARA INTERNASIONAL ZAINUDIN ABDUL MAJID - Ni Nyoman Yuliati; Lalu Jamhuri Hidayat; I Nengah Arsana (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This research aim to to know cash flow statement performance and growth of KokapuraSelaparang pursuant to year cash flow statement 2014-2018. this descriptive Research type with quantitative approach. Technique data collecting the used Technique interview and documentation. Research object in the form of balance data, loss and profit report, cash flow statement and allocation of division of Net income and also common picture of co-operation in year 2014-2018. Technique analyse data the used [is] cash flow ratio analysis which consist of Cash Flow Operation ratio ( AKO), Coverage Fund Flow ratio ( CAD), Coverage Cash ratio to Flower ( CKB), Coverage Cash ratio to Current Liabilities ( CKHL), Capital Expenditure ratio ( PM), Total Liabilities ratio ( TH), Free Clean Cash Flow ratio ( AKBB) and ratio Sufficiency of Cash Flow ( KAK). Monetary performance of KokapuraSelaparang in year 2014-2018 assessed from cash flow statement ratio expressed is good enough, its performance [in] telling good enough because from eight calculation of cash flow ratio above expressing that 3ratio fulfill standard 1, and only 4 ratio which [is] menu [do] not standard 1. Ratio which [do] not fulfill standard namely Cash Flow Operation ratio ( AKO), Coverage Cash to Current Liabilities ( CKHL) and Total Liabilities ( TH) and Sufficiency Of Cash Flow ( KAK). And ratio which have fulfilled standard namely Coverage Fund Flow ( CAD), Coverage Cash to Flower ( CKB), Capital Expenditure ( PM), and Free Clean Cash Flow ( AKBB. In this case Co-Operation unable to pay [for] ability of fluent obligation and and also indigent provide cash to fulfill its obligation. KokapuraSelaparanghave to can improve cash flow of activit operate for [so that/ to be] obligation short-range fufilled, maximizing and managing cash flow of got financing of member [so that/ to be] self-supporting.